Tying peasants to their land: The rise and fall of private property rights in historical Vietnam - Hoang-Anh Ho (The European Association for Banking and Financial History (EABH), 2020)
I present a theory to account for the emergence of land rights in a subsistence agricultural economy. An important feature is that, to maximize tax revenue, an authoritarian state must devise land rights to overcome the informational constraint in registering the population for tax collection. It can do so, given the state capacity is sufficiently high, by owning land and assigning cultivation rights (but not sale or transfer rights) to landless peasants to tie them to their land. The theory gives rise to a testable hypothesis, positing that private ownership of land is less prevalent in areas where population density is higher. In the early 19th century, the new Nguyen Dynasty of historical Vietnam carried out a land registry to establish formal land rights in the whole country. Exploiting this land registry, I discover that private ownership of land is less prevalent in areas where population density is higher. Furthermore, primary accounts and related historical studies show that the mechanism at work is in line with the proposed theory. Thus, the theory in question and the associated empirical evidence show that a strong state could reverse the general process in economic history whereby societies moved towards private land rights as population density increased and land became more scarce.
Keywords: D02; Q15; N45; 330; Land rights; Population density; Historical Vietnam